Urban watersheds : geology, contamination, and sustainable development - Kaufman, Martin M.; Rogers, Daniel T. (Daniel Timothy), 1959-; Murray, Kent S. (Boca Raton : CRC Press, 2011)
"This handbook presents 10 years of research on contaminants affecting lands and waters within heavily urbanized. It integrates research and professional practice from the fields of environmental geology, geochemistry, risk analysis, hydrology, and urban planning and offers knowledge on improving watershed management practices and urban development. It explains different aspects of urban land and water contamination; including sources, extents, and risks. The text includes case studies on successful and unsuccessful approaches to contaminant remediation, as well as practical methods for environmental risk assessment"--
-- Chapter 1 The Watershed Approach Chapter 2 Geology of Urban Watersheds Chapter 3 Water and the Hydrogeology of Watersheds Chapter 4 Conducting Subsurface Environmental Investigations in Urban Watersheds Chapter 5 Urban Geologic Mapping Chapter 6 Geologic Vulnerability Chapter 7 Common Contaminants in Urban Watersheds Chapter 8 Contaminant Fate and Transport Chapter 9 Metal Contamination in Urban Watersheds Chapter 10 Contaminant Risk Factors Chapter 11 Remediation: Techniques and Cost Chapter 12 Urbanization and the Disruption of Matter and Energy Flows within Watersheds Chapter 13 Pollution Prevention Chapter 14 Case Studies: Successful and Unsuccessful Redevelopment of Contaminated Sites Chapter 15 Science-Based Landscape Planning in Urban Watersheds Chapter 16 Attaining Sustainable Urban Watersheds
Includes bibliographical references and index.
Keywords: Urban runoff -- Management; Urban watersheds -- Protection; Water -- Pollution; Sustainable development; Cities and towns -- Environmental conditions; Urban pollution; Water Pollution; Water Movements; Water Supply; Water Purification; City Planning; Conservation of Natural Resources